Identification of Geothermal Potential in Block Ciasmara Sector II, Mount Salak Area, Based on the Correlation of the Active Directory Magnetotelluric (ADMT) and Self-Potential Methods - Permana, Nanda Ridki; Fadrian, Dhika Faiz; Gunawan, Belista; Primastika, Ayu Alvita; Zani, Fardhan Rafshan; Rahman, Fadhlur; Binonkan, Zahra Prameswari; Subekti, Faris Fawwas; Melly, Melly; Bahagia, Tazkia Izdihar; Harist, Ahmad Rizieq (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2023)
Indonesia possesses significant geothermal potential, with the largest share located in West Java, accounting for up to 21.7% distributed across 44 locations in 11 regencies. One such location with geothermal potential is in Block Ciasmara Sector II, the Mount Salak area, Bogor Regency, characterized by manifestations such as hot spring bathing pools. This research aims to understand the distribution of geothermal reservoirs in the study area, where these reservoirs contain hot fluids that can be harnessed for renewable energy generation. The methodology used in this research involves a correlation between the Active Directory Magnetotelluric (ADMT) and Self-Potential (SP) methods. A total of 3 ADMT measurements were conducted along tracks ranges from 5-8 meters, while the SP method involved 7 measurement points with coordinates distributed around the geothermal manifestations in the Mount Salak area. The data obtained were then visualized in 2D and 3D to gain insights into the distribution and orientation of the reservoir layers in the study area. The results indicate a correlation between the ADMT and Self-Potential methods. In Line 01 of the ADMT, located in the western part, there is a correlation with high potential difference values on the SP map ranges from 47.6-82.1 mV, suggesting the presence of tuff layers rich in alteration minerals. This is confirmed by the 2D ADMT modeling, which shows that the clay cap is thicker compared to Line 02 and Line 03, associated with the presence of alteration minerals in the clay cap. This correlation also applies to Line 03, which has low potential difference values ranges from 4.9-25.3 mV, indicating a response from lapilli rocks. This is corroborated by the 2D model, which reveals thickening of the lapilli rock layer on Line 03.Keywords: ADMT, Geothermal, Mount Salak, Reservoir, Self-Potential.